Co-cultivo de culturas iniciadoras potencialmente probióticas na elaboração de bebida vegetal - Ferreira, Iara (2021)
Fermented dairy products are the most common form of delivery of probiotic microorganisms. However, people with lactose intolerance, allergic to milk proteins or adherents of a vegan diet avoid ingesting such products. Thus, there is a need to offer these consumers an alternative to fermented dairy products. The objective of this work was to evaluate the performance of yeasts and bacteria in co-cultivation in the elaboration of a fermented beverage based on oats, sunflower seeds and almonds. The viability of the microorganisms after refrigerated storage for 28 days, the fermentative performance of the microorganisms and the sensory profile were evaluated. Three potentially probiotic yeast strains were used, being Pichia kluyveri (CCMA 0615), Pichia guilliermondi (CCMA 1753) and Debaryomyces hansenii (CCMA 1761), together with a lactic acid bacteria strain, Lactiplantibacillus plantarum (CCMA0743), also with characteristics probiotic potentials. L. plantarum was used alone and in co-culture with yeasts to ferment the substrates. Cells were inoculated at a concentration of 6.0 log CFU/mL for yeasts and 7.0 log CFU/mL for bacteria. The pH was measured at 0, 6, 12 and 24 hours of fermentation. At the same time, samples were taken for the enumeration of microorganisms and subsequent analysis. At the end of fermentation, the drinks were kept refrigerated at 4º C and samples were taken on days 7, 14, 21 and 28 days. Analysis was performed by High Performance Liquid Chromatography (HPLC) to identify carbohydrates, alcohols and organic acids. For volatiles, Gas Chromatography coupled with Mass Spectrometry was performed. Antioxidant analysis was performed by ABTS radical reduction and phosphomolybdenum complex methods. The sensory characterization of the drink was carried out using the Flash Profile method. All tested strains showed viability greater than 6.0 log CFU / mL, as recommended for food probiotic products, except for the P. kluyveri strain, which showed a reduction in total count. A reduction in the pH value was observed, from approximately 7 to, on average, 3.8, which occurred due to the production of organic acids by the inoculated microorganisms. Malic acid was completely converted into lactic acid through malolactic fermentation, which is the main metabolite produced during fermentation. Low concentrations of acetic and succinic acid were also detected. Ethanol was detected in all treatments with 24 hours of fermentation, however concentrations were lower than 5 g/L, the maximum value allowed for a drink to be considered non-alcoholic. 113 volatile compounds were detected, including alcohols, aldehydes, alkanes, alkenes, acids, ester, ether, ketones, phenol, amides and others. The antioxidant activity of the beverage reduced after the fermentation process. The microorganisms evaluated in this study proved to be suitable for the fermentation of non-dairy matrices, which, added to their promising probiotic characteristics, have great potential for application in the food industry. Among the treatments, the combination of L. plantarum + Debaryomyces hansenii proved to be the most promising treatment for the production of a probiotic fermented beverage of plant origin.